Membangun Warisan Ilmu: Perjalanan Pendidikan Islam Abad Ketiga dan Keempat Hijriyah - Mohammad Ridwan (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
The third and fourth centuries in the Hijri calendar are a significant period in Islamic history, marked by the emergence of the Umayyad and Abbasid caliphates and the expansion of the Islamic world from Spain to Central Asia. This era witnessed cultural transformation, shifts in power dynamics, and cross-cultural knowledge exchange that influenced the development of Islamic thought and education. This research aims to uncover the evolution of Islamic education during this period, including changes in educational approaches, philosophical thinking, and emphasis on scientific inquiry. Additionally, the study highlights the crucial role of strong governance, especially under the Abbasid Caliphate, in supporting scholarly culture and Islamic education. The research uses historical analysis, relying on primary sources such as historical texts to trace the development of Islamic education in the third and fourth Hijri centuries. The research findings indicate that government support, the establishment of madrasahs, and the promotion of Arabic as a scholarly language played a pivotal role in preserving and disseminating the intellectual heritage of Islam during this period.